2023
DOI: 10.3390/su15064823
|View full text |Cite
|
Sign up to set email alerts
|

The Interest Shown by Potential Young Entrepreneurs in Romania Regarding Feasible Funding Sources, in the Context of a Sustainable Entrepreneurial Education

Abstract: Among the most important factors that favor the development of a sustainable business environment are the sources of financing and the skills developed by the higher education system, according to recent studies. To align with these, several universities have started providing entrepreneurship knowledge. Are these sufficiently well-known by the students in Romania? The current paper aims to carry out an in-depth analysis of concepts. The primary objective of this study is to explore the most relevant sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Another study carried out in 2022 by Provident (a financial institution that offers its services to economically and/or socially vulnerable groups of Romanians) and which was entitled The Invisibles, concluded that small entrepreneurs at risk of poverty and social exclusion represent one of the six vulnerable groups in Romania, along with subsistence farmers, single-parent families, black workers, the unemployed between 55 and 64 years old, and pensioners at risk of poverty and social exclusion. Zamfirache et al (2023) conducted a study to evaluate the relationship between students' interest in entrepreneurship and the funding sources available to them for starting a business and they observed that European funds represent the most attractive funding source for students who want to become entrepreneurs. Therefore, social inclusion and self-efficacy represent strong motivations to overcome financial barriers.…”
Section: Of 14mentioning
confidence: 99%
“…Another study carried out in 2022 by Provident (a financial institution that offers its services to economically and/or socially vulnerable groups of Romanians) and which was entitled The Invisibles, concluded that small entrepreneurs at risk of poverty and social exclusion represent one of the six vulnerable groups in Romania, along with subsistence farmers, single-parent families, black workers, the unemployed between 55 and 64 years old, and pensioners at risk of poverty and social exclusion. Zamfirache et al (2023) conducted a study to evaluate the relationship between students' interest in entrepreneurship and the funding sources available to them for starting a business and they observed that European funds represent the most attractive funding source for students who want to become entrepreneurs. Therefore, social inclusion and self-efficacy represent strong motivations to overcome financial barriers.…”
Section: Of 14mentioning
confidence: 99%